Control of an AMB to zero static force - Michael CAPLE (The Japan Society of Mechanical Engineers, 2017)
Some active magnetic bearing (AMB) applications require that the mean, or static force exerted by the AMB is zero. Examples include hybrid fluid film - AMB bearing pairings, rotor midspan dampers, and statically indeterminant systems with stiff rotors and more than two radial AMBs. When the position of the rotor relative to magnetic center is not known precisely, this zero force requirement can be hard to meet. A low frequency periodic biasing scheme is developed which enables a controller to detect non-zero static force by sensing rotor motion at the bias carrier frequency. A theoretical basis establishes feasibility but also the potential for coupling between control signals and the periodic bias. Simulation demonstrates that an ad-hoc bias adaptation scheme can successfully drive the static component to zero while permitting otherwise conventional control. Experimental results on a small, single DOF test rig further demonstrate the ability to drive the AMB static force to zero while adding damping to the system. Identification of the system stability boundary provides insight on the structural requirements (mechanical stiffness versus magnetic negative stiffness) and the limitations on the control gain for the biasing scheme to work